Inflasi dalam IPO: Menelusuri Jejak Underpricing - Jufri Yandes; Destiana Destiana (Jurnal Eksplorasi Akuntansi, 2024)
The study explores whether in 2021 to 2022, the inflation rate has an influence on underpricing. The hypothesis testing approach process begins by passing the classical assumption test and linear regression analysis. Secondary data sources were obtained through the Indonesia Stock Exchange with a total population of 112, and 77 samples were selected based on specific criteria for use in the study. The results of the study reveal that from 2021 to 2022 inflation has an influence on underpricing. It is suspected that the inflation rate is used by investors as one of the decision indicators in investing in IPO shares in the period 2021 to 2022 which has an impact on the level of underpricing, in line with this because inflation can also be a driver or obstacle for economic growth, price stability, and especially in terms of investment decisions. This study is expected to provide a real contribution in the form of empirical data that is useful for issuers who list their shares and for future researchers and become a source of further recommendations.